ANALISIS NILAI TAMBAH KUE PIA PADA INDUSTRI RUMAH TANGGA KARYA âAN-NURâ DI KOTA PALU - Ahyadi, Ahyadi; Lamusa, Arifuddin (AGROTEKBIS, 2016)
This study aims to determine the added value derived from green beans when processed into cakes pia on Industry Household karya